How to write fast under pressure - Vassallo, Philip 1953- (IG library, 2010)
Anyone who regularly deals with work-related writing deadlines knows the kind of paralysis that can take over when there's too much to accomplish and not enough time to compose a clear sentence. This book contains an usable approach based on the mnemonic DASH, standing for the four critical components needed by writers, working under pressure.